Distance Learning’s (PJJ) Strategies In Islamic Religious Education by Using Online Learning (Case study at SMK Negeri 2 Salatiga) - Jariyah, Ainun; Nursikin, Mukh (Pascasarjana IAIN Kudus, 2021)
The outbreak of the Covid-19 Pandemic that has been present since around March 2019 presents a new policy in the learning process in schools, including in high schools. Learning shifts from face-to-face to online or online learning. Schools have their own policies for the selection of online media that will be used in online learning. One of the online media used is Microsoft Teams which was chosen by SMKN 2 Salatiga for online learning. This study aims to describe the conditions and strategies used in distance learning’s strategies (PJJ) by online learning In Islamic Religious Education at SMKN 2 SALATIGA. This study use a qualitative descriptive method through teachers and student’s interviews, documentation and observation. The results of this study indicate that, first, the PJJ’s planning on PAI subjects has been implemented through the making of RPP, training in Microsoft Teams applications and the provisions of infrastructure. Second, the implementation and participation of students in PJJ on PAI at SMKN 2 SALATIGA’s subjects showed a high percentage. The implementation stages is done through the Microsoft Teams application. Third, the learning’s evaluation was conducted using Google Form media, Microsoft Teams and Moodle. Remedial activities are given only during UAS.